Nina as just Nina: The life-creation of N.I. Petrovskaya in the light of A.P. Chekhov's “The Seagull” - Pavel F. Uspenskij (Литературный факт)
The article examines the life-creation of the writer and translator Nina Petrovskaya, whose tragic love relationship with Valeriy Bryusov became a vivid literary fact of Russian symbolism. It is generally believed that Petrovskaya created her own life based on Bryusov’s novel The Fiery Angel, in particular, Renata, the protagonist, became her biographical model. This interpretation of the text of Petrovskaya’s life was largely set by the writer herself, who identified with Renata in correspondence with Bryusov. The reasons for merging with a literary character and the motives for her own renaming seem to be a natural consequence of Bryusov’s life-creation experiment. Such an explanation deprives Petrovskaya of subjectivity and turns her into a passive victim of the symbolist master, without taking into account her life choice — the desire to be in a painful relationship and prolong it. As shown in the article, Petrovskaya’s life-creating model goes back not so much to Bryusov’s text as to Chekhov’s The Seagull. Focusing on Nina Zarechnaya and finding herself in a similar life conflict as the heroine of the play, Petrovskaya voluntarily created a tragic story from her life. This model text for Petrovskaya also explains her onomastic gesture: renaming herself Renata is associated with the self-renaming of Zarechnaya as a seagull. The article also addresses the topic “Chekhov and Russian Modernism” and demonstrates that Chekhov’s texts could be perceived by symbolists as life-creating models.